Copper-catalyzed aerobic oxidative coupling of ketones with P(O)–H compounds leading to β-ketophosphine oxides. Issue 7 (26th April 2017) - Fu, Qiang; Yi, Dong; Zhang, Zhijie; Liang, Wu; Chen, Suyuan; Yang, Lu; Zhang, Qiang; Ji, Jianxin; Wei, Wei
Abstract : A facile copper-catalyzed one-pot method for the synthesis of β-ketophosphine oxides has been developed via aerobic oxidative coupling of ketones with P(O)–H compounds assisted by TBSOTf at room temperature. Abstract : A facile and efficient copper-catalyzed one-pot method for the construction of β-ketophosphine oxides has been developed via aerobic oxidative coupling of various ketones with P(O)–H compounds assisted by TBSOTf ( t -butyldimethylsilyl triflate). Through this methodology, a series of β-ketophosphine oxides can be easily obtained in moderate to good yields with favorable functional group tolerance under very mild conditions. Isotope-labeling experiments suggested that the carbonyl oxygen atom of β-ketophosphine oxides originated from dioxygen.